The Role of the Carboxyl-Terminal Sequence of Tau and MAP2 in the Pathogenesis of Dementia - Xie, Ce; Miyasaka, Tomohiro (Frontiers in Molecular Neuroscience, 2016)
Dementia includes several of diseases characterized by acquired and irreversible brain dysfunctions that interfere with daily life. According to the etiology, dementia can be induced by poisoning or metabolic disorders, and other cases of dementia have a clear pathogenesis. However, half of neurodegenerative diseases have an unclear pathogenesis and etiology. Alzheimer’s disease (AD), Lewy body dementia and frontal-temporal dementia are the three most common types of dementia. These neurodegenerative diseases are characterized by the appearance of the following specific protein inclusions: amyloid beta and tau in AD; α-synuclein in Lewy body dementia; and tau, TDP-43, or FUS in frontal-temporal dementia. Thus far, studies on the pathogenesis of dementia mainly focus aberrant inclusions formed by the aforementioned proteins. As a historically heavily studied protein tau is likely to be associated with the pathogenesis of several neurodegenerative diseases that cause dementia. The role of tau in neurodegeneration has been unknown for many years. However, both pathological and genetic analyses have helped tau become gradually recognized as an important factor in the pathogenesis of tauopathy. Currently, especially in the field of AD, tau is attracting more attention and is being considered a potential target for drug development. In this review, previously discovered biochemical and pathological features of tau are highlighted, and current opinions regarding the neurotoxicity of tau are summarized. Additionally, we introduce key amino acid sequences responsible for tau neurotoxicity from our studies using transgenic Caenorhabditis elegans. Finally, a new hypothesis regarding the roles of microtubule-associated protein 2 and tau in the pathogenesis of tauopathy is discussed.